Focusing Technique for Holographic Subsurface Radar Based on Image Entropy - Jung, Haewon; Yun, Dal-Jae; Kang, Hoon (Applied Computational Electromagnetics Society Journal (ACES), 2021)
An image focusing method for holographic subsurface radar (HSR) is proposed herein. HSR is increasingly being utilized to survey objects buried at shallow depths and the acquired signals are converted into an image by a reconstruction algorithm. However, that algorithm requires actual depth and material information or depends on human decisions. In this paper, an entropy-based image focusing technique is proposed and validated by numerical simulation software package based on finite-difference time-domain method and experiment. The resulting images show good agreement with the actual positions and shapes of the targets.